The effects of music arousal level and tempo on card game players’ risk-taking and EEG mental state among introverts and extroverts / Ho Hao Yi - Ho , Hao Yi (2020)
This is an experimental quantitative study which examined the effects of music arousal level and tempo on card game players’ risk-taking and EEG mental state among introverts and extroverts. A total of 20 male participants (through selection of 10 introverts and 10 extroverts) aged between 18 – 29 voluntarily participated by playing the card game In-Between. All participants put on the NeuroSky® MindWaveTM Mobile EEG device and played the game while being exposed to various music conditions. The conditions were no-music (control) condition, and a set of both high-arousal (hereafter HA) and low-arousal (hereafter LA) music manipulated to three different tempi, which are 100% (normal tempo), 175% (faster tempo), and 75% (slower tempo). In terms of gameplay risk-taking among the arousal level conditions, findings showed that there were only significant differences between HA and LA music conditions, but insignificant between the music and no-music conditions. Among the tempo conditions, overall risk taken were highest during the highly-arousing and extremely-fast music tempo condition, while overall risk taken were lowest during the lowly-arousing and original music tempo condition. In terms of gameplay EEG mental state, attention and meditation levels were highest when the music stimuli were optimally-arousing, in which the optimal arousal level of extroverts is generally higher than introverts, in accordance with the optimal arousal hypothesis. However, over-arousal impairs mental state and task performance, in which its effects will be much more detrimental among introverts.